2020
DOI: 10.1101/2020.10.10.20210096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracorporeal Blood Purification in moderate and severe COVID-19 patients: a prospective cohort study

Abstract: Introduction: COVID-19 is characterised by hyperinflammation and coagulopathy. Severe cases often develop respiratory distress, requiring mechanical ventilation and critical cases progressing to ARDS. Control of hyperinflammation has been proposed as a possible therapeutic avenue for COVID-19; extracorporeal blood purification (EBP) modalities offer an attractive mean to ameliorate maladaptive inflammation. With this work, we describe the longitudinal variation of parameters of systemic inflammation in critic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In a time-series analysis of 44 consecutive COVID-19 cases treated with the AN69ST (oXiris) cytokine adsorbing hemodiafilter a decrease in acute phase proteins was demonstrated with a reduction in IL-6 levels and an observed mortality of 36.3% across the cohort. 109 In a further study on 5 patients using the AN69ST filter a reduction in cytokines levels and improvement of hemodynamic status was also observed and similarly in 37 patients in a further single-center study a reduction in expected mortality was also seen (8.3% compared with the expected rate as calculated by APACHE IV). 110,111 Several studies have reported benefits on the use of the hemadsorption filter Cytosorb whereby improvements in catecholamine use as well as decreases in inflammatory markers were seen.…”
Section: Extracorporeal Blood Purificationmentioning
confidence: 59%
“…In a time-series analysis of 44 consecutive COVID-19 cases treated with the AN69ST (oXiris) cytokine adsorbing hemodiafilter a decrease in acute phase proteins was demonstrated with a reduction in IL-6 levels and an observed mortality of 36.3% across the cohort. 109 In a further study on 5 patients using the AN69ST filter a reduction in cytokines levels and improvement of hemodynamic status was also observed and similarly in 37 patients in a further single-center study a reduction in expected mortality was also seen (8.3% compared with the expected rate as calculated by APACHE IV). 110,111 Several studies have reported benefits on the use of the hemadsorption filter Cytosorb whereby improvements in catecholamine use as well as decreases in inflammatory markers were seen.…”
Section: Extracorporeal Blood Purificationmentioning
confidence: 59%
“…Similarly, reduced of increased cytokines levels, hemodynamic stabilization and improvement of SOFA and APACHE scores was observed in five covid-19 patients after therapy with CVVHDF using Oxiris filter [68] . In addition, an observational study of 44 patients, therapy with Oxiris filter showed a reduction of the overexpressed inflammatory mediators but without a clear benefit on mortality rate [69] . On the contrary, Kang et al, proposed that CRRT with Oxiris filter when used in critically ill Covid-19 patients without AKI, may not attenuate the cytokine storm and should be used with caution in this group of patients [70] .…”
Section: Oxiris and Polymethyl Methacrylate (Pmma) Membranesmentioning
confidence: 99%
“…Various modalities for KRT are available, including high‐volume hemofiltration (HVHF), with treatment selection driven by available resources, expertise, and patient's hemodynamic stability (Figure 3) [22–24]. Though several studies and evident literature follow adult treatment for AKI exacerbated by COVID‐19, children present as a novel population with unique physiological differences thus creating a need for extensive clinical trials to identify the safety and efficacy of various KRT modalities [25].…”
Section: Pathophysiologymentioning
confidence: 99%